Using Geocomputation and R as a Methodological Tool: Re-Creating Spatial Structures of the Irish Republican Army in Early Twentieth-Century Ireland. - Kavanagh, Jack (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2025)
This article explores how geocomputational processes can be utilised to re-create historical spatial boundaries using Irish historical data. For this study, a series of spatial objects representing Irish Republican Army (IRA) brigades in County Limerick during 1921 were re-created in R using the Military Service Pension Collection (MSPC), one of the largest archival projects released by the Military Archives of Ireland. Using density equalising projections via cartograms, a series of analyses of the demography of the IRA was undertaken using these internal boundaries. County Limerick along the western seaboard of Ireland was chosen as a case study, as it represents a mixed urban/rural environment outside of the three major population centres on the island of Ireland: Cork, Dublin and Belfast. By deploying a geocomputational approach via the programming language R, this article provides a roadmap for historians and humanities scholars in general to reproduce these findings and spatial boundaries for future research.